Never without an Intercessor: the good news about the Judgment - Venden, Morris L. (Pacific Press Pub. Association, 1996)
Do you worry about the judgment?Can you picture standing alone before the judgement throne of God, answering for your angel's complete record of every word, deed, and thought of your entire life? Can you picture it without shaking? Are you sure your belief in salvation by faith in Jesus alone can hold up to this scene?And what about living without an intercessor? Should we be storing up righteousness by battery or by habit or by momentum--enough righteousness to carry us through a time when we will be on our own?If these are the pictures in your mind, pastor and best-selling author Morris Venden is here to tell you--you've got it all wrong.Venden shares with us again how the bad news of the judgement relates to the good news of the gospel. - PrefaceIntroduction: Don't Read This Book IfThe Bad News of the GospelThe Trouble With GraceThe Bad News About GraceThe Bad News About ObedienceThe Good News About JudgmentThe Preadvent Judgement Is BiblicalNever Without an IntercessorLiving Without SinningOvercoming Known SinThe Bad News About the WeddingRevelation 3:5 for SinnersGood News for LegalistsGood News for PhariseesThe Good News About AtonementAppendix